Value Chain Analysis of Jackfruit Chips in Green Supply Chain Management Perspective Using the Value Chain Operations Reference Method - Dania, Wike Agustin Prima; Nurfitriani, Edria Anniar; Septifani, Riska (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
AbstractA green supply chain is a concept that integrates environmental aspects in the supply chain system. This study aims to identify the value chain stages affecting the environment and to determine the level of economic impact on the jackfruit chips value chain at CV XYZ. This research used Value Chain Operations Reference (VCOR) method to analyze value chain activities. Carbon emissions and total costs were calculated at the build, acquire, and fulfill stages from suppliers and enterprises. The analysis results showed that the highest environmental impact was at the build stage which produces carbon emissions of 133,314.8 kg CO2. The frying process contributed the highest carbon emission, which was 117,600 kg CO2. CV XYZ was in the intolerable region condition in the Global Impact matrix. The resulting carbon footprint is 16.84 kg CO2/kg with a unit cost of 0.32 €/kg. The recommendation strategy was substituting firewood with liquefied petroleum gas (LPG) to lower carbon emissions by up to 40%.Keywords: carbon emission, Green Supply Chain Management, Value Chain Operation Reference        AbstrakGreen supply chain adalah sebuah konsep yang mengintegrasikan aspek lingkungan pada sistem rantai pasok. Penelitian ini bertujuan untuk mengidentifikasi tahapan rantai nilai yang berdampak pada lingkungan dan menentukan tingkat dampak ekonomi pada rantai nilai keripik nangka di CV XYZ. Penelitian ini menggunakan metode Value Chain Operations Reference (VCOR) untuk menganalisis aktivitas rantai nilai. Emisi karbon dan total biaya dihitung pada tahap build, acquire, dan fulfill dari supplier dan perusahaan. Hasil analisis menunjukkan bahwa dampak lingkungan tertinggi terdapat pada tahap build yang menghasilkan emisi karbon sebesar 133.314,8 kg CO2. Proses penggorengan memberikan kontribusi emisi karbon paling tinggi, yaitu 117.600 kg CO2. CV XYZ terletak pada kondisi intolerable region dalam Global Impact matrix. Jejak karbon yang dihasilkan adalah 16,84 kg CO2/kg dengan biaya unit sebesar 0,32 €/kg. Strategi yang direkomendasikan adalah penggantian kayu bakar dengan liquefied petroleum gas (LPG) yang dapat menekan tingkat emisi karbon hingga 40%.Kata kunci: emisi karbon, Green Supply Chain Management, Value Chain Operation Reference